From a materially produced to a socially constituted space: A proposal for a new research perspective on public service provision and infrastructures in rural areas based on a relational theory of space - Jessica Baier (Spatial transformation: Processes, strategies, research design, 2022)
This article uses research in relation to the provision of public services and infrastructures to support the thesis that primarily one particular perspective on space - namely a material or quantifying perspective - is reflected in current empirical research. The article thus proposes the use of the concept of relational space by Martina Löw (2001) in empirical research to improve our empirical understanding of the space relevant for local people. To conclude, potential insights gained are outlined on the basis of the conceptualisation of a study of private colleges in rural areas in Germany.
urn:nbn:de:0156-08910630; hdl:10419/251347; https://econpapers.repec.org/RePEc:zbw:arlfob:19
Keywords: 710; Public service provision; social infrastructure; rural areas; relational space; private colleges